Peningkatan Budaya Literasi Siswa melalui Implementasi Model Pembelajaran Read-Answer-Discuss-Explain-and-Create (RADEC) - Nana Suryana; Wahyu Sopandi (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
One of the educational problems faced today is that it has not succeeded in realizing a culture of literacy. Weak reading skills, perhaps this is because education still emphasizes aspects of routine skills and mere memorization. So, a learning model is needed that can facilitate students to have a literacy culture. To overcome this problem, it was developed through the Read-Answer-Discuss-Explain-and-Create (RADEC) learning model. This study aims to describe the improvement of students' literacy culture through the implementation of the Read-Answer-Discuss-Explain-and- Create (RADEC) learning model. The research method used is a Quasi-Experimental Research One-Group Pretest-Posttest Design with the research subjects of 26 fifth grade students of Pondoksari Sukaresik State Elementary School, Tasikmalaya, West Java, Indonesia. The results showed that literacy culture can be improved through the implementation of the RADEC learning model of 5.1.